Social Integration and Terminal Decline in Life Satisfaction Among Older Japanese - Nakagawa, Takeshi; Hülür, Gizem (The journals of gerontology. Series B, Psychological sciences and social sciences, 2020)
Well-being typically exhibits pronounced deteriorations with approaching death, with sizeable interindividual variations in levels and changes. It is less well understood how psychosocial factors contribute to these individual differences. We examined whether and how social integration is associated with terminal trajectories of well-being, indexed as life satisfaction. Data were drawn from 1,119 deceased Japanese participants of a 15-year longitudinal study (age at death: M = 79.2 years; SD = 7.7 years; 43.1% women). Life satisfaction, structural and functional features of social integration (e.g., frequency of contact with family and nonfamily, and perceived overall support, respectively), sociodemographic characteristics, and physical function were assessed. Social integration predicted individual differences in terminal decline in life satisfaction, after controlling for age at death, gender, education, and physical function: More diverse social relationships were associated with higher levels of life satisfaction at 1 year before death. In addition, individuals who exhibited more decline in social participation and perceived less support showed more pronounced decline with increasing proximity of death. This study suggests that social integration plays a protective role in late-life well-being and that sustaining an active social life and supportive social interactions may help mitigate terminal decline in well-being.